The Effectiveness of Nearpod-Based Learning Media on the Biology Learning Outcomes of 11th Grade Students at UPT SMA Negeri 10 Sidenreng Rappang - Uli Rainilda; Usman M; Hasanuddin Hasanuddin; Muhammad Takdir (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the effect of using Articulate Storyline 3 learning media on student learning outcomes in the subject of Arts and Culture in class XII UPT SMA Negeri 10 Sidenreng Rappang. The research method used is quantitative with a true experimental type. The research sample consisted of 36 students who were divided into two groups, namely the experimental group using Articulate Storyline 3 learning media and the control group using conventional learning methods. Data collection techniques were carried out through learning outcome tests in the form of multiple choices and documentation. Data were obtained through learning outcome tests and analyzed using statistical tests to see the differences between the two groups. The results showed that there was a significant difference between the learning outcomes of students who used Articulate Storyline 3 learning media and those who did not use it. The average value of the experimental group was higher than the control group (87.11> 68.88). This proves that the use of Articulate Storyline 3 as a learning medium can improve student learning outcomes in the subject of arts and culture.